Qiraat dalam Mushaf Kuno dan Mushaf Standar - Zarkasi Afif (Lajnah Pentashihan Mushaf Al-Qur'an, 2017)
Abstract Studies on the aspects of qiraat or reading in the ancient manuscript have not been widely done. This article describes the study of three ancient manuscripts of the La Galigo Museum collection of Makassar, South Sulawesi, and compares them to the qiraat or reading used in the current Indonesian Standard Manuscript. The three ancient manuscripts being studied are using the qiraat (readings) of Imam Nafi ‘. They are different from the Indonesian Standard Manuscript which is written by following the qiraat of Imam’ Asim from the narration of Hafs. These three manuscripts were copied in the 19th century. There is an assumption that at the time of the copying of these mushafs, the qiraat that developed in the archipelago had followed the qiraat of Imam Asim as it is nowadays. One of the ancient manuscripts lists the sign of (x) on the words (lafaz) whose readings are different, and this ancient manuscript also lists the qiraat of Imam ‘Asim on the edge of the page. This study can provide a concrete description of the level of scholarship of the Qur’an in the past, especially in the science of qiraat, has reached the advanced level - or even more advanced than that of today, because today publication of the Mushaf does not include different qiraat.